1992
DOI: 10.1302/0301-620x.74b3.1587902
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally produced fractures of articular cartilage and bone. The effects of shear forces on the pig knee

Abstract: (1) splitting of uncalcified cartilage; (2) splitting at the subchondral plate; (3) subchondral fracture; and (4) infra-articular fracture.When shear force was applied at high speed but with low energy, the articular cartilage surface was the first to crack. At low speed and low energy, splits occurred in the deeper layers first. As the energy increased, both loading conditions eventually resulted in similar open lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 10 publications
3
22
0
1
Order By: Relevance
“…The speed and energy of shear force will influence the pattern and extent of cartilage failure, leading to chondral delamination injuries that vary with regard to the zone of cartilage that is involved and the presence or absence of violation of the cartilage surface (65). Excessive shear force can produce components, with material properties that include stiffness and permeability (41).…”
Section: State Of the Artmentioning
confidence: 99%
“…The speed and energy of shear force will influence the pattern and extent of cartilage failure, leading to chondral delamination injuries that vary with regard to the zone of cartilage that is involved and the presence or absence of violation of the cartilage surface (65). Excessive shear force can produce components, with material properties that include stiffness and permeability (41).…”
Section: State Of the Artmentioning
confidence: 99%
“…10,37 However, various reports indicate that cartilage is more prone to injuries during shear loading of the joint. 38 Excessive shear strain causes abundant collagen fibril strain that has been shown to correspond accurately with areas of collagen destruction leading to cartilage damage. 39 Our results showed that the tibial plafond exhibited 70% higher shear moduli in comparison with the talar dome.…”
Section: Disparity In Articulating Surfaces Of Anklementioning
confidence: 99%
“…3 Several impact models have been used to study the processes leading to cartilage degeneration. The most common trauma caused by impact loading are fissures at the cartilage surface in the middle of the impacted zone, which extend downward at approximately 45 degrees into the superficial, [4][5][6][7][8] middle, 9,10 or deep 11,12 zones. Excessive shear stresses, 13 excessive tensile stresses, 14 or excessive principal strains, [15][16][17][18] might cause the formation of these cracks.…”
Section: Introductionmentioning
confidence: 99%